Determinants of innovation outcomes: The role of institutional quality. (December 2022) - Sharma, Abhijit; Sousa, Cristina; Woodward, Richard
Abstract: This paper uses unconditional quantile regression analysis to interrogate the effects of institutional quality on innovation outcomes. We assess important determinants of innovation such as property rights (including enforcement of intellectual property rights), human resources within R&D and high-technology exports. Regarding intellectual property rights, while most previous research focuses on patent strength ( de jure or book law), we focus on de facto patent enforcement. Using data from the World Bank, the Heritage Foundation and a new patent enforcement index, we construct a panel of fifty countries covering 1998–2017. Our analysis reveals important new insights including the strongly negative impact of patent enforcement and human resources within R&D on less innovative economies, and the varying impacts across quantiles for key variables such as high-technology exports. We find that both stronger institutions and patent enforcement are not necessarily the best route to boosting innovation, especially in economies where existing innovative capacity is weak Highlights: Impact of institutional quality varies across the distribution of innovation outcomes. Strict patent enforcement inhibits patent activity in least innovative and technologically developed countries. Better quality institutions are not necessarily the best route to boosting innovation.